Cardio-omentopexy Reduces Cardiac Fibrosis and Heart Failure After Experimental Pressure Overload - Wang, Jian (Ann Thorac Surg, 2018)
BACKGROUND. The pedicled greater omentum has been shown to offer benefit in ischemic heart disease for both animal models and human patients. The impact of cardio-omentopexy in a pressure overload model of left ventricular hypertrophy (LVH) is unknown. METHODS. LVH was created in rats by banding the ascending aorta after right thoracotomy (n = 23). Sham surgery was performed in 12 additional rats. Six weeks after banding, surviving LVH rats were assigned to cardio-omentopexy by left thoracotomy (LVH + Om, n =8) or sham left thoracotomy (LVH, n = 8). Sham rats also underwent left thoracotomy for cardio-omentopexy (Sham + Om, n = 6); the remaining rats underwent sham left thoracotomy (Sham, n = 6). RESULTS. Echocardiography 10 weeks after cardio-omentopexy revealed LV end-systolic diameter, cardiomyocyte diamter, and myocardial fibrosis in the LVH group were significantly increased compared with the LVH + Om, Sham + Om, and Sham groups (p < 0.01). LV ejection fraction of the LVH group was lower than theLVH + Om group (p < 0.01). Gene expression analysis revealed significantly lower levels of sarcoendoplasmic reticulum calcium adenosine triphosphatase 2b in LVH rats than in the LVH + Om, Sham + Om, and Sham groups (p < 0.01). In contrast, collagen type 1 α 1 chain, lysyl oxidase-like protein 1, nuclear protein-1, and transforming growth factor- β1 in the LVH group were significantly higher than in the LVH + Om cohort (p < 0.01), consistent with a reduced fibrotic phenotype after omentopexy. Lectin staining showed myocardial capillary density of the LVH group was significantly lower than all other groups (p < 0.01). CONCLUSIONS. Cardio-omentopexy reduced cardiac dilation, contractile dysfunction, cardiomyocyte hypertrophy, and myocardial fibrosis, while maintaining other molecular indicators of contractile function in this LVH model.